Countering ‘the poverty of thought in novels’: radical authorship and The Royal Captives by Ann Yearsley - Andrews, Kerri (Romanticism on the Net, 2007)
AbstractThe publication of Ann Yearsley’s only novel, The Royal Captives in 1795 is an important moment for our current understanding of what it was possible to publish during the political chaos of the 1790s.Yearsley’s later career has been largely ignored by critics; her biographer makes only a brief mention of the novel’s existence, and few others have engaged with it at all. Yet in 1795, Yearsley burst into novel writing, earning an astonishing £200 from the Robinsons for what would be her only novel. Cheryl Turner has noted that this sum is significant in itself; it was rare for such a sum to paid, particularly for a novel, and few women ever earned this much. It was nearly as much as Frances Burney earned for Cecelia, and was more than Elizabeth Inchbald received for Nature and Art. The first aim of this paper will therefore be to give Yearsley’s novel the fullest treatment it has yet received. It will also consider more generally Yearsley’s later career, in particular the performance, then publication of her only play Earl Goodwin early in the decade, before placing The Royal Captives in the context of the wider British reaction to events in France. By making use of Yearsley’s letters to her friends and patrons in Yorkshire, Eliza Dawson and Wilmer Gossip, in which she relates her thoughts about novel-reading. this paper will seek to create a sense of Yearsley’s project as a novelist, and how this engages with national debates. The novel itself will be considered alongside contemporary reviews and more recent critical responses which will provide the context for a reading which aims to demonstrate the fundamental radicalism of The Royal Captives. The paper will then conclude with an assessment of the wider implications of Yearsley’s move into novel writing, where it is suggested that a reconsideration of mid-1790s print culture is needed.